Solid state bioconversion of lignocellulosic residues by Inonotus obliquus for production of cellulolytic enzymes and saccharification. (January 2018) - Xu, Xiangqun; Lin, Mengmeng; Zang, Qiang; Shi, Song
Graphical abstract: Highlights: I. obliquus is a novel promising source for lignocellulosic conversion. Optimization of process parameters promoted the cellulase production in SSF. The cellulase enzymes worked well under thermophilic and acidophilic conditions. The best performances of cellulases produced on Day 12 in straw saccharification. The saccharification efficiency was dependent on lignocellulolytic enzyme activities. Abstract: White rot fungi have been usually considered for lignin degradation and ligninolytic enzyme production. To understand whether the white rot fungus Inonotus obliquus was able to produce highly efficient cellulase system, the production of cellulolytic enzyme cocktails was optimized under solid state fermentation. The activities of CMCase, FPase, and β-glucosidase reached their maximum of 27.15 IU/g, 3.16 IU/g and 2.53 IU/g using wheat bran at 40% (v/w) inoculum level, initial pH of 6 . 0 and substrate-moisture ratio of 1:2.5, respectively. The enzyme cocktail exhibited promising properties in terms of high catalytic activity at 40–60 °C and at pH 3.0–4.5, indicating that the cellulolytic enzymes represent thermophilic and acidophilic characteristics. Saccharification of raw wheat straw and rice straw by the cellulolytic enzyme cocktail sampled on Day 12 resulted in the release of reducing sugar of 130.24 mg/g and 125.36 mg/g of substrate after 48 h of hydrolysis, respectively.